The total quality management practices in Yemeni Public Universities - Hussein Al-Amri, Ali Abdullah (2012)
There is a mutual relationship between the prosperity of a nation and the quality of education it provides to its people. Quality education improves standard of living of people by enhancing the performance of engines of economic development. This study focuses on the practice and application of Total Quality Management (TQM) in Yemeni universities. A questionnaire was developed after a careful and thorough review of the related literature and consultations with experts. The questionnaire was administered to universities academy staff. The study was performed based on a survey method for collecting data. A total of 262 questionnaires usable surveys were received. Correlation Pearson, t-test, One-way ANOVA were applied to analysis the gathered data from the questionnaire. The data were analyzed using computer- mediated (Statistical Package for Social Sciences) (SPSS). According to the analysis of TQM made in Yemen universities using statistical methods; Cronbach Alpha was high enough to a value of 0.96. Unfortunately, the Yemeni public universities have low turnout of TQM practice.